Companionable thinking (Medicine Anthropology Theory, 2020)
The paper takes up three themes that emerge from the commentaries on the book, 'Affliction: Health, Disease, Poverty': (a) the relevance of neighborhood as the right scale at which to render the relation between health, disease, and poverty; b) the ordinary as an interrogation of the normal; and c) the relation between subjectivation and subjectivity. Knitting together the qualitative and the quantitative as well as advocacy and research, this essay comments on Georges Canguilhem’s notions of the normal and the pathological, and of disease as an experiment with life. It also provides a commentary on the default position often assumed in the literature on subjectivity that treats it as the residue, as that which subjectivation cannot encompass. These different themes are joined within an overarching question: how do we learn to see ethnographically what is before our eyes?